THE INFLUENCE OF THE USUAL HOLDING SOLUTIONS ON Hyacinthus orientalis CUT FLOWER VASE LIFE - Lucian RĂUS; Mariana VOLF; Diana Elena BOLOHAN (Journal of Applied Life Sciences and Environment)
In this study, four holding solutions very often used by florists and the final consumer were tested to analyse their impact on the development of the inflorescence, as well as the elongation, weight and degree of bending of the hyacinth flowers. The use of these solutions has a general character, and the flower species react differently due to both their genetics and the conditions in which they were cultivated, handled and stored. To verify the effectiveness of the preservative solutions on Hyacinthus orientalis vase life, four solutions were prepared with 2% sucrose and none or one of the follow-ing antimicrobial substances: sodium hypochlorite, acetic acid and ascorbic acid. During the study, measurements were made on the weight, elongation of the floral stems, chlorophyll content of the leaves and vase life days. The vase life of the hyacinths in this experiment was 5 days, except for the flowers from the 2% sucrose holding solution, which started to wilt on day 5. On day 6, the flowers showed signs of senescence. The increase in the length of the inflorescence stem showed significant differences for the sucrose + ascorbic acid holding solution, with a maximum of 0.8 cm on day 4. However, the interest was not to maximise the elongation of the floral stem but to slow down this process since elongation leads to the bending of the stem, causing it to require additional support.